Giant hepatic hemangioma: An unusual cause of gastric compression - Egemen Özdemir; Sami Akbulut; Koray Kutlutürk; Sezai Yılmaz (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Özdemir E, Akbulut S, Kutlutürk K, Yılmaz S. Giant hepatic hemangioma: An unusual cause of gastric compression. Turk J Gastroenterol 2019; 30(10): 930-1.